The Effect of Various Probiotics in Sangkuriang Cat Fish (Clarias gariepinus) on Health Status and Performans Production - Anhar Faisal Fanani; Sulis Anjarwati; Nurul Fajrih (Jurnal Perikanan dan Kelautan, 2018)
Probiotics are very important for cultivation because of their role in improving the health status of fish, increasing the body's resistance to disease, growth rate, improving intestinal morphology and balance of the microflora. The study aimed to compare commercial probiotics with probiotics from fermented milk using kefir seeds in an effort to improve health, growth rate and efficiency of sangkuriang catfish feed. The research material used 5-7cm long sangkuriang catfish as many as 400 tails. The study used a completely randomized design (CRD) with 4 treatments and 5 replications, namely P0:Control (feed without addition of probiotics), P1: Feed + 5% Probiotics A (King Grameh), P2: Feed + 5% Probiotics B (Em4), P3: Feed + 5% Probiotics C (Kefir). Each experimental unit consisted of 20 fish. The parameters observed in this experiment were growth rate, FCR and feed efficiency. Treatment with various types of probiotics has a significant effect (P <0.05) on FCR, feed efficiency, and growth rate. However, the FCR in treatments T1 and T2 did not show significant differences, and on feed efficiency and growth rate on T1 were not significantly different. The conclusion of this study is that the provision of kefir probiotics is able to show better production results.